Penyimpangan Tumbuh Kembang pada Anak dari Orang Tua yang Bekerja - Eny Pemilu Kusparlina; Eddy Warsito (FORIKES, 2022)
Growth and Development Deviation in Children with Working Parents. Children is the nation precious asset. As the future generation, high quality children is needed to achieve bright future of the nation. Less attention to the growth and development supported factor due to the working parent causes growth and development deviation in children.The aim of this study was to identify the relationship between parenting style of working parent with growth and development deviation in children. The study cross sectional study involved in 73 respondents in Taman district, Madiun City, using stratified random sampling. The results were 77% children had good growth and 56.2% children had appropriate development. 23% children had minimun one abnormal growth indicator and 4.1% children was suspected to had development deviation. Data analyzes showed that there was no significant relationship between parenting style and growth (p= 1.000, α= 0.05), parenting style and development (p= 1.000, α= 0.05), parent working status and growth (p= 0.497, α= 0.05), parent working status and development (p= 0.901, α= 0.05), time of working and growth (p= 0.497, α= 0.05), time of working and development (p= 1.000, α= 0.05). This study implies that working parent is not burden factor for children to grow up and develop optimally.Keywords: child aged 0-72 months; children growth & development; parenting style